Niejednorodność obserwacji w modelach logitowych - Kapłon, Robert (Heterogeneity in Logit Models, 2006)
In order to model heterogeneity in the logit models one can use latent class analysis as well as finite mixture distribution. Frequently, these two names are used interchangeably. Taking into account the fact that these methods were originally meant for different goals, the aim of this paper is to compare these methods - pointing out similarities and differences.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (17); 2006; nr 1123, s. 95-106